Development of Android-Based Learning Media SiBudiman for Biography Text Material in Class X Students - Arifin, Ahsanul; Werdiningsih, Dyah; Rani, Abdul; Asror, Abdul Ghoni (International Journal of Language Teaching and Education, 2026)
Educational technology advancement demands learning methodologies aligned with interactive, autonomous ecosystems. This research developed SiBudiman, an Android-based learning media employing hybrid architecture (MIT App Inventor frontend + Google Sites backend cloud storage) for Biography Text instruction (Merdeka Curriculum Phase E, Grade X). The hybrid design produced a lightweight application (≤10 MB) with rich multimedia content, representing a methodological innovation addressing storage limitations while maintaining content quality, a critical gap in literature where prior offline Android applications consumed 50-100 MB. Using 4D model (Define, Design, Develop, Disseminate), expert validation encompassed content, language, and media dimensions. Quasi-experimental pre-post control group design tested effectiveness (n=33 experimental, n=30 control). Validation achieved 86.7% average (content 90%, language 90%, media 80%), with iterative revision addressing identified media design improvements. Practicality testing demonstrated 93.4% student approval rate and 76.8% teacher acceptance. Effectiveness analysis controlling for baseline differences (pretest: experimental M=81.21 vs. control M=76.33) revealed significant posttest gains (experimental M=90.91 vs. control M=82.33; t(61)=4.84, p<0.001). Normalized Gain analysis showed superior learning efficiency (experimental N-Gain=0.5161 vs. control N-Gain=0.2535), indicating SiBudiman facilitated 51.61% of available improvement potential versus 25.35% for conventional methods. Cohen's d=1.26 (very large effect size) positioned SiBudiman within highest-efficacy technology-enhanced learning interventions reported in literature (typical d=0.4-0.6). These results demonstrate SiBudiman successfully overcame infrastructure constraints while significantly enhancing analytical comprehension of biography text structure, linguistic features, and exemplary values, with sustained effectiveness across diverse student achievement levels.